MODEL AGROSCIENCE KIDS LAB SEBAGAI INOVASI PEMBELAJARAN IPA DI WILAYAH 3T - Retno Wuri Sulistyowati; Mega Suteki; Diah Harmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Science learning in 3T areas (underdeveloped, frontier, and outermost regions) continues to face various limitations, particularly in the availability of contextual teaching materials and practice-based learning approaches. This study aims to develop and describe the AgroScience Kids Lab model as an environmental-based innovation in science learning at the elementary school level. The research employed a qualitative approach with a case study design conducted at SD Inpres Tambat, Merauke. Data were collected through observations, interviews, and documentation, and analyzed using thematic analysis techniques. The findings reveal that the AgroScience Kids Lab model consists of four main components: (1) thematic educational gardens as living laboratories, (2) contextual science experiment media, (3) a mini seed bank, and (4) an Outdoor Science Corner. This model enhances student engagement, experiential understanding of scientific concepts, and awareness of food security and environmental sustainability. Furthermore, the model demonstrates strong potential as an innovative learning approach that is adaptable to resource-limited conditions in 3T regions.